TIME MANAGEMENT RELATIONSHIP WITH ACHIEVEMENT MOYIVATION USING STATISTICAL TEST - RATNA PUSPITA INDAH; NOVEMY TRIYANDARI NUGROHO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
The purpose of this research is to know the relationship between the management of a lot of time with motivation of the creation was who were high performing what the students are the faculty of of computing the university of the ambassador of surakarta .The kind of research this is correlation analysis at the pearson candy businesses .Percent of the population that had been established in this research is that an entire kind what the students are the faculty of computer science the university of the ambassador of surakarta as many as 500 what the students are. Unsupported sample taken by applying a technique simple random sampling so acquired unsupported sample obtained was that 94 what the students are . In this research data collection uses the method kuosioner ( ) other of any economic indicators .Based on the results of testing in ibm spss statistics 23 obtained that data observations berdistribusi normal for variables reaches as high as the management of the time and prepare the motivation of the creation was after that of last year .That the data used in berdistribusi normal so testing to see sidnifikansi between management time ( x ) with motivoasi who were high performing ( y ) use correlation test pearson candy businesses .The results of correlation test showing that the significance of the between management time ( x ) with the motivation who were high performing ( y ) is 0,779 > 0,01 who meant that there was no significant correlates between both variables reaches.